HUBUNGAN TINGKAT PENGETAHUAN MAHASISWA TATA RIAS UNESA TERHADAP SIKAP PENGGUNAAN TABIR SURYA - Rekhananda , Karin; Dwiyanti, Sri; Usodoningtyas, Sri; Kusstianti, Nia (Jurnal Tata Rias, 2024)
This study aims to investigate the relationship between the knowledge level of UNESA cosmetics students and their attitudes toward sunscreen use. This quantitative correlational research involved 64 cosmetics education students from UNESA who had taken cosmetology courses. Purposive sampling was employed, and data collection utilized questionnaires distributed to respondents. Product moment correlation analysis measured the relationship between knowledge and attitudes. Results showed 93.53% of respondents demonstrated high knowledge, while 70.23% exhibited inadequate attitudes toward sunscreen use. Pearson correlation (2-tailed) yielded 0.0001, with a strength coefficient of 0.657, indicating significant and strong correlation between knowledge and attitudes. Therefore, a strong relationship exists between UNESA cosmetics students' knowledge and their attitudes toward sunscreen use. Keywords: Knowledge, Attitude towards Use, Sunscreen.